ANALISIS PENDAPATAN DAN TINGKAT KESEJAHTERAAN RUMAH TANGGA PETANI KOPI DI KECAMATAN SUMBER JAYA KABUPATEN LAMPUNG BARAT - Yuliani, Evi (Program Studi Agribisnis, 2023)
The level of income is one indicator of the achievement of the welfare of a farmer household. This study aims to analyze (1) the production, costs, and income of coffee farming, (2) the income structure of coffee farmers' households, and (3) the level of welfare of coffee farmers' households in Sumber Jaya District, West Lampung Regency. The choice of location was determined purposively. Sampling was done by proportional random sampling method (proportional random sampling) and obtained a total sample of 46 farmers. The data analysis method used is coffee farming income analysis, farmer household income analysis, inequality indicators based on the Gini Ratio value, and poverty indicators according to Sajogyo (1977) based on farmer household expenditures. The results show that the income sources of coffee farmers are quite diverse, where income from coffee farming contributes 45.50% to the total income of farmers. The level of income inequality of coffee farmers is based on the Gini Ratio value of 0.40 which shows the level of income inequality in the medium category. In addition, according to Sajogyo (1977), the poverty rate of farmer households is in the moderate category of 56.53%, decent living 34.78%, near poor 6.52%, and poor 2.17%.